Aqueous‐Processed Polymer/Nanocrystals Hybrid Solar Cells: The Effects of Chlorine on the Synthesis of CdTe Nanocrystals, Crystal Growth, Defect Passivation, Photocarrier Dynamics, and Device Performance. Issue 1 (4th January 2017) - Zeng, Qingsen; Chen, Zhaolai; Liu, Fangyuan; Jin, Gan; Du, Xiaohang; Ji, Tianjiao; Zhao, Yue; Yue, Yuanyuan; Wang, Haiyu; Meng, Dedong; Xie, Tengfeng; Zhang, Hao; et al.
Abstract : High‐quality nanocrystals (NCs) are vital to achieve high‐performance polymer/nanocrystals hybrid solar cells (HSCs). However, in‐depth investigation on aqueous CdTe NCs related properties is extraordinarily insufficient, thus, limiting the further improvement of the device performance of aqueous‐processed HSCs. In this work, the effects of chlorine (Cl) on the synthesis of aqueous CdTe NCs, crystal growth, defect passivation, photocarrier dynamics, and device performance are systematically investigated. We demonstrate that the surface trap states of as‐prepared aqueous CdTe NCs can be effectively passivated by introducing Cl ions in the synthetic process. In addition, it is discovered that Cl in the as‐prepared CdTe NCs can promote CdTe grain growth in the sintered process to reduce grain boundaries. The aqueous‐processed poly(p‐phenylenevinylene) (PPV)/CdTe HSCs are used as prototype solar cells to systematically study the influence of Cl on the electrical properties of CdTe NCs. The power conversion efficiency (PCE) of the HSCs based on CdTe NCs with optimal Cl content is improved by a factor of 25 compared to that based on the CdTe NCs without Cl. The ultrafast transient absorption (TA), transient photovoltage (TPV) and light intensity dependent open circuit voltage ( Voc ) and short‐circuit current density ( Jsc ) measurements are implemented to systematically investigate the influence of Cl on photocarrier dynamics, including charge transfer, lifetime, and carrier recombination. The researches on carrier recombination indicate that the presence of Cl can effectively reduce nongeminate recombination to improve charge extraction efficiency, thus leading to elevated device performance. Furthermore, it is demonstrated that the residual Cl after annealing also plays important roles in the highly efficient polymer/CdTe HSCs by passivating the trap states on the grain boundaries of CdTe NCs. Finally, this work suggests that the photovoltaic performance of HSCs can be further promoted through adopting improved passivation methods to reduce trap states on the grain boundaries in the future work. Abstract : The effects of chlorine on the synthesis of aqueous CdTe nanocrystals, crystal growth, defect passivation, photocarrier dynamics, and device performance are systematically investigated. The device performance of aqueous‐processed polymer/CdTe hybrid solar cells is dramatically improved after incorporating CdTe NCs with Cl. This is attributed to the reduced nongeminate recombination leading to improved charge extraction efficiency.